The westernization of the East: an opportunity for development or a fallacy? - Bocatto, Evandro; Perez-de-Toledo, Eloisa (My University, 2022)
The paper re-conceptualizes the terms West and East, arguing that West is related to development whereas East is in development. From the westernization metaphor, the article asks: Does the East intend to become the West? Content analyses and comparison of cases allow for the interpretation of countries’ intentions regarding economic, political, social, and environmental orientations of governments, institutions, and businesses. The paper concludes that the East is unlikely to find the ‘right’ model of growth by replicating the West because the Western model has mistakenly assumed unlimited resources for growth, among other reasons. To benchmark Western development is a fallacy to the East. Tradeoffs occur as the East chooses the Western economic model as its benchmark. The paper discusses the role of social and technological innovations in business and society as possible, albeit limited, solutions.
Keywords: westernization; democracy; social inequality; environment